2014
DOI: 10.1159/000370317
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Serum Ferritin Lead to Adequate Hemoglobin Levels and Good Survival in Hemodialysis Patients

Abstract: Background: The optimal level of serum ferritin (s-ft) for anemia control and good survival in hemodialysis (HD) patients remains unclear. A 10-year survey was performed to clarify the appropriate quantities of s-ft and investigate the relationships among s-ft, transferrin saturation (TSAT), and mortality in HD patients. Methods: HD outpatients (n = 125) treated with erythropoiesis-stimulating agents (ESA) were followed for 10 years. The ESA and low-dose iron supplement dosages were adjusted to maintain the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 40 publications
2
27
1
Order By: Relevance
“…This MRI study suggests that the standard maximal monthly IV iron dose should be lowered to 250 mg to lessen the risk of iron overload in dialysis patients and seems to be in good agreement with the 3 recently published long-term epidemiological studies [12][13][14]87]. The worldwide nephrology community is also rediscovering the ingenious, cautious Japanese strategy of iron therapy, which maintains optimal hemoglobin levels (somewhat lower than in western countries) with minimal use of IV iron products and lower ferritin levels [21,88]. Rostoker et al have recently speculated that the better overall survival of Japanese hemodialysis patients, as compared with US and European patients, might be, at least in part, related to lower use of IV iron products and, thus, less iron overload although these findings may also be related to less inflammation (partially) due to a very high quality of dialysis in Japan [3].…”
Section: Prevention Of Iron Overload In Dialysis Patientssupporting
confidence: 80%
“…This MRI study suggests that the standard maximal monthly IV iron dose should be lowered to 250 mg to lessen the risk of iron overload in dialysis patients and seems to be in good agreement with the 3 recently published long-term epidemiological studies [12][13][14]87]. The worldwide nephrology community is also rediscovering the ingenious, cautious Japanese strategy of iron therapy, which maintains optimal hemoglobin levels (somewhat lower than in western countries) with minimal use of IV iron products and lower ferritin levels [21,88]. Rostoker et al have recently speculated that the better overall survival of Japanese hemodialysis patients, as compared with US and European patients, might be, at least in part, related to lower use of IV iron products and, thus, less iron overload although these findings may also be related to less inflammation (partially) due to a very high quality of dialysis in Japan [3].…”
Section: Prevention Of Iron Overload In Dialysis Patientssupporting
confidence: 80%
“…The Japanese Society for Dialysis, out of concern for iron overload, proposed as early as 2011 that minimal IV iron (up to 650 mg in the induction phase) be given to hemodialysis patients and only in cases of true iron deficiency (ferritin < 100 μg/L), and also warned against maintenance IV iron therapy . This careful strategy of iron repletion allowed adequate hemoglobin levels with low ferritin, moderate transferrin saturation without any detrimental effect on survival and was again advocated this year for Japanese dialysis populations …”
Section: Iron Products Should Be Used With Caution In Dialysis Hepatimentioning
confidence: 99%
“…Data from a longitudinal study also revealed an association between increased mortality and lower baseline Hb levels (relative risk, 1.78, Hb <8 g/dL vs. Hb 11–11.99 g/dL) . Furthermore, among HD patients receiving ESA, those with lower baseline serum ferritin levels and TSAT >20% had a lower risk of death compared with those with higher baseline ferritin levels and TSAT ≤20% (HR, 0.16 [ P = 0.004], 95% CI 0.05─0.55, TSAT >20% [serum ferritin 30–80 ng/mL] vs. TSAT ≤20%) . Similarly, a study by Kuragano et al showed that among HD patients treated with ESA and iron over a 2‐year period, the risk of death was higher for those who had an upward trend from low to high ferritin (HR, 6.18; 95% CI 1.99─19.12) during the study period or with high‐amplitude fluctuations in ferritin levels (HR, 3.75; 95% CI 1.15─12.28) compared with those with low ferritin levels .…”
Section: Synthesis Of Resultsmentioning
confidence: 93%
“…Although none of the 10 studies reporting mortality data evaluated mortality rate due to anemia in CKD, seven studies reported all‐cause mortality in HD patients. Mortality rate ranged from 7.2–13.3% in stage 5 CKD patients (time to endpoint, 18–25 months) to 35.2% in CKD patients on dialysis receiving ESA treatment to maintain 10≤ Hb <11 g/dL (time to endpoint, 10 years) . Okazaki et al reported that among HD patients, increased mortality was associated with ESA resistance (hazard ratio [HR], 4.204, highest [10.0–33.7] vs. lowest [2.0–5.0] erythropoietin resistance index [ERI] tertile; 95% CI 1.173–15.065) .…”
Section: Synthesis Of Resultsmentioning
confidence: 99%